Location of arm draining lymph node in relation to breast cancer radiotherapy field and target volume. (April 2019) - Wang, Wei; Ward, Rachel; Jia, Dan; Ashworth, Simon; Estoesta, Edgar; Moodie, Trevor; Ahern, Verity; Stuart, Kirsty; Ngui, Nicholas; French, James; Elder, Elisabeth; Farlow, David
Highlights: Our study demonstrates that the vast majority of ARM nodes (72%) are outside the tangential whole breast radiotherapy fields. And all the ARM nodes were within the axillary radiotherapy fields covering level 1–4 axillary volumes according to the ESTRO contouring guideline, and complete shielding of the humeral head according to the EORTC consensus did not lead to sparing of the ARM nodes. We recommend a prospective study is needed to examine the oncological safety of ARM node-sparing axillary radiotherapy and its potential to reduce the risk of arm lymphoedema. Abstract: Background: Lymphoedema of the arm following axillary surgery or radiotherapy remains a significant side effect affecting some women after breast cancer treatment. Axillary reverse mapping (ARM) is a technique used to identify the lymph node draining the arm (ARM node). Our study aim was to examine the location of the ARM nodes in relation to target volumes and treatment fields for breast cancer radiotherapy. Materials and methods: Eighteen breast cancer patients underwent lymphoscintigraphy of contralateral arm (left 10, right 8) and SPECT CT scan on a research study. Patient position for the SPECT CT scan approximated the position used for radiotherapy. Using MIM software™, the ARM node for each subject was contoured on the SPECT CT and verified by a nuclear medicine physician. The CT component of the SPECT CT was then transferred to ECLIPSE™ radiotherapy planning software, and the contralateral breast and axilla were contoured on this CT scan according to the ESTRO contouring guideline. Two radiotherapy plans were generated for each subject using standard tangential IMRT technique at a dose of 50 Gy in 25 fractions, one treating contralateral breast alone, the other treating contralateral breast and contralateral axilla level 1–4. The ARM node was considered "within the radiotherapy field" if the mean dose received by the ARM node was more than 50% of the prescribed dose: i.e., 25 Gy. Results: One right-sided subject had 2 ARM nodes, all others had 1 ARM node. All ARM nodes (left 10, right 9) were located within level 1 of the axilla. For the subject with 2 ARM nodes, the node that received a higher dose was used for the analysis. The mean dose received by the ARM node in the whole breast radiotherapy plans ranged from 0.8 to 45.5 Gy, with a median of 10.9 Gy. The mean dose received by the ARM node in the whole breast and axilla plans ranged from 43.4 to 52.5 Gy, with a median of 49.3 Gy. In the whole breast radiotherapy plans, only 5 out of 18 ARM nodes were found to be "within radiotherapy field", and only 2 ARM nodes received more than 40 Gy. In the breast and axilla plans, all 18 ARM nodes were "within radiotherapy field" and all received more than 40 Gy. To better visualise the locations of ARM nodes, all left sided ARM nodes were then mapped onto a CT set from one of the left-sided subjects, and all the right sided ARM nodes mapped onto one of the right-sided subjects, and digitally reconstructed radiograph (DRR) for radiotherapy fields were produced. Conclusions: Our study demonstrates that the vast majority of ARM nodes (72%) are outside the tangential whole breast radiotherapy fields. In our study, all the ARM nodes were within the axillary radiotherapy fields covering level 1–4 axillary volumes according to the ESTRO contouring guideline, and complete shielding of the humeral head according to the EORTC consensus did not lead to sparing of the ARM nodes. A prospective study is needed to examine the oncological safety of ARM node-sparing axillary radiotherapy and its potential to reduce the risk of arm lymphoedema.